Efficacy of Eimeria tenella (Oocyst and Sporozoite) Proteins as a Vaccine in Broilers Against Coccidiosis - Al-Idreesi , Suhair R.; Kweider, Mahmoud; Katranji, Mahmad M. (International Journal of Poultry Science, 2013)
The protective efficacy against homologous challenge in chickens evaluated by using two proteins of a (Sporozoite) and (Oocyst) from Eimeria tenella. Immunization was applied on 3rd and 16th day of age subcutaneously with this two types of protein in separate groups at dose (25μg per chicken). Vaccinated birds were challenged at 30th day of age, demonstrated that sporozoite protein could provide chickens with protection rate around 99.2-99.5%, while oocyst protein gives 67-69% protection, number of oocysts and cecal lesion from chickens in the immunized groups with sporozoite protein decrease significantly and this protein was more effective from another groups. The body weight gain not affected (higher) in sporozoite immunized groups when compared with oocyst protein immunized groups and control positive groups, also we estimated ACI which was demonstrated that sporozoite protein was very effective while the oocyst protein was slightly effective.